Proportion of single-chain recombinant tissue plasminogen activator and outcome after stroke. (6th December 2016) - Leys, Didier; Hommet, Yannick; Jacquet, Clémence; Moulin, Solène; Sibon, Igor; Mas, Jean-Louis; Moulin, Thierry; Giroud, Maurice; Sagnier, Sharmila; Cordonnier, Charlotte; Medeiros de Bustos, Elisabeth; Turc, Guillaume; et al.
Abstract : Objective: To determine whether the ratio single chain (sc)/(sc + 2 chain [tc]) recombinant tissue plasminogen activator (rtPA) influences outcomes in patients with cerebral ischemia. Methods: We prospectively included consecutive patients treated with IV rtPA for cerebral ischemia in 13 stroke centers and determined the sc/(sc + tc) ratio in the treatment administered to each patient. We evaluated the outcome with the modified Rankin Scale (mRS) at 3 months (prespecified analysis) and occurrence of epileptic seizures (post hoc analysis). We registered Outcome of Patients Treated by IV Rt-PA for Cerebral Ischaemia According to the Ratio Sc-tPA/Tc-tPA (OPHELIE) under ClinicalTrials.gov identifier no. NCT01614080. Results: We recruited 1, 004 patients (515 men, median age 75 years, median onset-to-needle time 170 minutes, median NIH Stroke Scale score 10). We found no statistical association between sc/(sc + tc) ratios and handicap (mRS > 1), dependency (mRS > 2), or death at 3 months. Patients with symptomatic intracerebral hemorrhages had lower ratios (median 69% vs 72%, adjusted p = 0.003). The sc/(sc + tc) rtPA ratio did not differ between patients with and without seizures, but patients with early seizures were more likely to have received a sc/(sc + tc) rtPA ratio >80.5% (odds ratio 3.61; 95% confidence interval 1.26–10.34). Conclusions: The sc/(sc + tc) rtPA ratio does not influence outcomes in patients with cerebral ischemia. The capacity of rtPA to modulate NMDA receptor signaling might be associated with early seizures, but we observed this effect only in patients with a ratio of sc/(sc + tc) rtPA >80.5% in a post hoc analysis.